2014
DOI: 10.1371/journal.pone.0104635
|View full text |Cite|
|
Sign up to set email alerts
|

Polymorphism of 9p21.3 Locus Is Associated with 5-Year Survival in High-Risk Patients with Myocardial Infarction

Abstract: ObjectiveThe rs10757278, rs1333049 and rs4977574 are single nucleotide polymorphisms (SNPs) of chromosome 9p21 locus associated with a prevalence of acute coronary syndromes (ACS). Reports concerning their association with long-term outcome after an ACS are equivocal. The aim of our study was to investigate the association of the 9p21.3 locus with 5-year overall mortality in patients with ST-elevation myocardial infarction (STEMI).Materials and methodsWe performed a retrospective analysis of data collected pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
2
0
2
Order By: Relevance
“…They found that 9p21.3 locus is associated with five-year survival in high-risk patients with myocardial infarction [20]. Zeng et al investigated whether rs10757278 was associated with acute coronary syndrome (ACS) in a Chinese Han population [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that 9p21.3 locus is associated with five-year survival in high-risk patients with myocardial infarction [20]. Zeng et al investigated whether rs10757278 was associated with acute coronary syndrome (ACS) in a Chinese Han population [21].…”
Section: Discussionmentioning
confidence: 99%
“…Szpakowicz et al performed a retrospective analysis of data collected prospectively in two independent registries of consecutive patients to investigate the association of the 9p21.3 locus (rs10757278, rs1333049 and rs4977574 polymorphisms) with five-year overall mortality in patients with ST-elevation myocardial infarction [ 20 ]. They found that 9p21.3 locus is associated with five-year survival in high-risk patients with myocardial infarction [ 20 ]. Zeng et al investigated whether rs10757278 was associated with acute coronary syndrome (ACS) in a Chinese Han population [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Однако тенденция в виде меньшей доли носителей генотипа АА в подгруппах с неблагоприятными сердечно-сосудистыми исходами -сохраняются. Полученные данные о протективном эффекте rs10757278 в отношении риска развития сердечно-сосудистых осложнений ОКС в течение пятилетнего наблюдения соотносятся с результатами зарубежных исследований [13].…”
Section: результаты и обсуждениеunclassified
“…В частности, была продемонстрирована строгая связь генетических пре-дикторов с отдаленными исходами у наиболее тяже-лых больных ИМ -имевших многососудистое пора-жение КА или стратифицированных по шкале GRACE [16,17].…”
Section: рисunclassified